Enamel Hypoplasia in a Medieval Population from Slaboszewo - Krem, Marta; Piontek, Janusz (Anthropological Review, 1996)
Enamel hypoplasia in 68 individuals from a medieval cemetery of Slaboszewo (North-Western Poland) was analysed. Individual ages at defect development were assessed. Sex differences as well as mean age at death of individuals affected and unaffected were calculated. Possible causal factors have been discussed.